Bone in intestinal polyp-a curious observation (Bangladesh Journal of Medical Science, 2013)
We report rare phenomena of ossification in benign colon polyp. An adult woman presented with occasional bleeding per rectum for which she was investigated. A polypoid rectal swelling was detected and histolopathology revealed an inflammatory polyp with osteoid formation. The case is presented for its rarity and available literature is reviewed. DOI: http://dx.doi.org/10.3329/bjms.v12i4.16669 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 453-455